Esophageal Suspension Method for Hand-Sewn Esophagojejunostomy After Totally Laparoscopic Total Gastrectomy: A Simple, Safe, and Feasible Suturing Technique - Huang, Chao; Zhao, Jiefeng; Liu, Zitao; Huang, Jun; Zhu, Zhengming (Frontiers in Oncology, 2020)
Background: Totally laparoscopic total gastrectomy (TLTG) not only is difficult to operate but also has high technical requirements and a long learning curve. Therefore, it has not been widely carried out yet, and esophagojejunostomy is one of its difficulties. Relevant studies have shown that intracorporeal hand-sewn esophagojejunostomy is safe, feasible and low-cost, but it is complicated and time-consuming and requires a high-suture technique. This study introduces a simple, safe and feasible hand-sewn technique. Methods: The clinical data of 32 patients with the esophageal suspension method for hand-sewn esophagojejunostomy (suspension group) after TLTG were collected from February 2018 to June 2019. During the same period, 32 patients with traditional hand-sewn esophagojejunostomy (traditional group) after TLTG were used as the control group. Results: The operative time, anastomosis time, exhaust time and hospitalization time of the suspension group were shorter than those of the traditional group. The intraoperative blood loss in the suspension group was less than that in the traditional group. There were no postoperative complications associated with the suspension group. Conclusion: For those who have some experience in laparoscopic suture technique, the esophageal suspension method for hand-sewn esophagojejunostomy after TLTG is a simple, safe, and feasible suture technique.